Técnica de Frenkel para el control de la marcha en adulto mayor, 2018 - Castillo Bejarano, Bryan Andrés (2019)
The following research work was carried out under the bibliographic collection type, the theme to work is the Frenkel technique for walking control in the elderly, 2018, with the aim of identify the benefits of the Frenkel technique for the walking control of the elderly adult patient, improving the lifestyle when this pathology is present. Due to the research subject it is not frequently applied in our working field, there are few updated bibliographical resources that sustain the research, however, it was possible to find 13 bibliographical sources that will allow us to compare the results obtained and discusse them in a more detailed way. The inclusion criteria play a decisive role in the investigation, allowing us to delineate with more detail the investigation. We have accepted the most relevant articles published in the last 10 years on this research theme and that have been approved through the PEDro scale with a higher rating than 6/10 to confirm the validity of their publications. After the investigation and after the corresponding discussion of the authors the objective was achieved, the Frenkel technique helped to improve the balance, march and decreased the present of falling risk, through its three exercises phases: rest, sitting and standing, demonstrating by means of the assessment with the Tinetti scale in the intermediate and final phase, that the older adult population obtained positive results from the first sessions, their results being reflected in the independence of their daily life activities.